Incorporating the Chinese language into schools in the Kingdom of Saudi Arabia | إدراج اللغة الصينية في مدارس المملكة العربية السعودية - Sarhan | سرحان, Yasser Abdullah | ياسر عبد الله; Al-Juhani | الجهني, Abdul Rahman bin Marshoud | عبد الرحمن بن مرشود; Al-Ansari | الأنصاري, Abdul Wahid | عبد الواحد; Al-Hassan | الحسن, Hussein Muhammad | حسين محمد; Al Zamanan | آل زمانان, Saleh bin Ali | صالح بن علي; Al-Wadi'i | الوادعي, Abdullah bin Ali | عبد الله بن علي; Al-Muhaimid | المحيميد, Muhammad bin Odeh | محمد بن عودة (Center for Research and knowledge networking | مركز البحوث والتواصل المعرفي, 2023)
In February of 2019, Saudi Crown Prince Mohammed bin Salman visited China during his Asian visit, and during the visit, His Highness agreed with the Chinese side to start developing a plan to include the Chinese language as a curriculum in Saudi educational levels, in an effort to strengthen the bonds of relationship Chinese Saudi Arabia. | في فبراير من عام 2019م, قام ولي العهد السعودي الامير محمد ابن سلمان بزيارة الصين في أثناء زيارته الآسيوية, و خلال الزيارة قام سموه بالاتفاق مع الجانب الصينيعلى البدأفي وضع خطة لادراج اللغة الصينية كمقرر دراسي في المراحل التعليمية السعودية, سعيا من سموه في تعزيز أواصر العلاقة السعودية الصينية.